KURZWÖRTER IM DEUTSCHEN RAKETENUND ARTILLERIEWORTSCHATZ: STRUKTURELLE UND TRANSLATORISCHE ASPEKTE - Sobczak, Michał (Acta Neophilologica, 2018)
This his article is devoted to the analysis of the structure of German abbreviations used in the field of artillery and rocket industry and their Russian equivalents registered in a specialized translation dictionary published in 1982. The analytical part of the paper is preceded by a theoretical background, in which selected problems and inconsistencies within the definition of acronyms and abbreviations are touched upon. Then, lexicographical problems of the lexical units in question are pointed out. The article concludes with possible translation solutions of the analyzed abbreviations and acronyms.